Dissemination of the Methicillin-resistant Staphylococcus aureus Pediatric Clone (ST5-T002-IV-PVL+) as a Major Cause of Community-associated Staphylococcal Infections in Bedouin Children, Southern Israel. Issue 3 (March 2019) - Rokney, Assaf; Baum, Moti; Ben-Shimol, Shalom; Sagi, Orli; Anuka, Einav; Agmon, Vered; Greenberg, David; Valinsky, Lea; Danino, Dana
Abstract : Introduction: Pediatric community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections are emerging worldwide. High CA-MRSA carriage rates were previously described in healthy Bedouin children. We assessed demographic, clinical and molecular characteristics of pediatric MRSA infections in southern Israel. Methods: The Soroka University Medical Center laboratory serves the entire population of southern Israel, divided into 2 ethnic groups, Bedouins and Jews. All in-hospital MRSA clinical isolates from children 0 to 18 years old obtained in 2016 were included. Health care–associated and community-associated infections were defined according to the Centers for Disease Control and Prevention case definition. All isolates were evaluated for staphylococcal cassette chromosome, Panton–Valentine leukocidin, S. aureus protein A type, pulsed field gel electrophoresis and antimicrobial susceptibility testing. Results: Overall, 95 MRSA isolates (18% of all S. aureus ), with 25 different MRSA strains, were identified. Twenty-eight isolates (29.5% of MRSA) belonged to the pediatric clone, rarely observed in Israel, staphylococcal cassette chromosome IV, Panton–Valentine leukocidin positive, S. aureus protein A type 002. All isolates demonstrated identical pulsed-field-gel-electrophoresis fingerprints. Eighty-two percent of infections caused by this clone were community-acquired, mainly observed in young Bedouin children, causing skin and soft-tissue infections. The new clone infection characteristics were similar to those of other CA-MRSA. All isolates of the pediatric clone were susceptible to trimethoprim/sulfamethoxazole, ciprofloxacin, gentamicin, tetracycline, rifampicin and vancomycin; 17.8% were nonsusceptible to erythromycin and clindamycin. Conclusion: The pediatric CA-MRSA clone, previously described only in sporadic cases in Israel, is emerging among healthy, young Bedouin children, typically causing skin and soft-tissue infections. Isolates are susceptible to a variety of non–beta-lactam antibiotics.